The immediate and long-term effects of time perspective on Internet gaming disorder - Lukavská, Kateřina (Journal of behavioral addictions, 2018)
Backgrounds and aims This study focuses on the role of time perspective (TP) in Internet gaming disorder (IGD). An inventory-based study on 377 massive multiplayer online role playing game players was conducted, followed by a 3-year-follow-up in which 48 active players from the original sample participated. We proposed that TP factors (negative TP and future positive TP) will influence either the current presence of IGD symptoms or the further development of IGD over time. In other words, the effect of TP is stable. Finally, game usage patterns were analyzed in the sense of changes in playing time and IGD symptoms in gamers after 3 years. Methods To access the variables, two scales were administered through online inventory, the Zimbardo Time Perspective Inventory-short, and Charlton and Danforths' Core Addiction Scale, both in 2012 (N = 377) and 2015 (N = 48). The amount of time that gamers usually spent playing were obtained through self-reports. Results The study's primary presumptions were confirmed. Both negative TP and future positive TP were confirmed as significant predictors of the presence of IGD symptoms, either immediately or in the following 3 years. Data on game usage showed a significant decrease in playing time and IGD symptoms between year 0 and year 3 of the study.
Keywords: Young Adult; Male; internet; Middle Aged; longitudinální studie; mladý dospělý; Adolescent; následné studie; time perspective; Child; dítě; Adult; longitudinal; Aged; dospělí; mužské pohlaví; senioři; Internet; návykové chování; mladiství; Follow-Up Studies; Video Games; lidé; ženské pohlaví; Humans; Time Perception; Behavior, Addictive; Internet gaming disorder; Longitudinal Studies; massive multiplayer role-playing games; Female; lidé středního věku; videohry; vnímání času